Customer service engineering in construction - Shevchuk, K.I. (Ways to Improve Construction Efficiency, 2020)
The article considers the role and mission of the customer service in engineering activities during the design and implementation of investment and construction projects. The essence of engineering, its legal definition, types of engineering at different stages of investment projects are revealed, it is determined that the main purpose of cost engineering is to stimulate for economical work, which is possible through the use of effective engineering solutions. The review of theoretical approaches and methodical recommendations to the concept of "engineering activity", "cost engineering", ways of estimation and formation of effective service of the customer on engineering activity at stages of designing, erection of construction objects, commissioning is carried out. Cost engineering has been identified as an integral part of engineering. The legal support of engineering activities is considered. It is proposed to classify engineering activities according to the functional approach in accordance with the stages of investment projects, namely: pre-project engineering - pre-project stage, project engineering - maintenance of project documentation, construction engineering - engineering activities during construction of facilities - commissioned and further operation, cost engineering - cost optimization at all stages of the investment project, not just at the design stage. The author's classification will allow to coordinate the types of engineering activities with the main stages of implementation of investment and construction projects and will facilitate the customer's services to choose areas for improvement of ongoing projects. It has been proposed for the leading Ukrainian universities to conduct advanced training and introduce the second level of higher education in higher education in the specialty "Сost Engineering in Construction".